Fördert mathematisches Modellieren die Motivation in Mathematik? Befunde einer Interventionsstudie bei HauptschülerInnen (mathematica didactica, 2012)
In this article we present results of the research project „Strategies for teaching unterstanding in and through modelling“. In this research project 13 teaching units were developed in order to foster mathematical modelling of pupils at the German Hauptschule. In a pre-post-control-group-design a variety of variables on student-level and teacher-level were considered. Here we focus on the effect of the teaching units on motivational variables. The results of our study generally indicate a decrease of learning motivation during the school year. As an effect of the teaching units, however, the decrease of learning motivation could be blocked with regard to four of the five indicators of learning motivation.